A review on advances in green treatment of glycerol waste with a focus on electro-oxidation pathway - Ahmad, M.S. (Elsevier Ltd, 2021)
Over the past decades, research efforts are being devoted into utilizing the biomass waste as a major source of green energy to maintain the economic, environmental, and social sustainability. Specifically, there is an emerging consensus on the significance of glycerol (an underutilised waste from biodiesel industry) as a cheap, non-toxic, and renewable source for valuable chemicals synthesis. There are numerous methods enacted to convert this glycerol waste to tartronic acid, mesoxalic acid, glyceraldehyde, dihydroxyacetone, oxalic acid and so on. Among these, the green electro-oxidation technique is one of the techniques that possesses potential for industrial application due to advantages such as non-toxicity process, fast response, and lower energy consumption. The current review covers the general understanding on commonly used techniques for alcohol (C1 & C2) conversion, with a specific insight on glycerol (C3) electro-oxidation (GOR). Since catalysts are the backbone of chemical reaction, they are responsible for the overall economy prospect of any processes. To this end, a comprehensive review on catalysts, which include noble metals, non-noble metals, and non-metals anchored over various supports are incorporated in this review. Moreover, a fundamental insight into the development of future electrocatalysts for glycerol oxidation along with products analysis is also presented. Â© 2021 Elsevier Ltd